Demutru Values as Habitus in Building Religious and Community Life in Grime Nawa - Baransano, Imelda; Lattu, Izak Yohan Martriks; Suwarto; Tampake, Tony Robert Christian; Karubaba, Hendrika, Yovania (International Journal of Educational Research Excellence (IJERE), 2024)
Research purposes This is to describe, Demutru Values as local wisdom of the Grim e Nawa Community in Ja y apura Regency-Papua and Demutru Values as Habitus in building religious and social life in Grim e Nawa Regency Jayapura-Papua. The research method used in this research is qualitative research with descriptive analysis using an ethnographic approach. Data collection techniques use observation, interviews and documentation methods. The research subjects were traditional leaders, community leaders, young men and women leaders and parents in society. Data analysis techniques through data reduction, data provision and drawing conclusions. The results of this research found that Demutru's values as a habitus in building religious and social life in Grime Nawa, Jayapura-Papua Regency are: First, values as a manager who organizes all activities in society. Second, the value of being a servant who solves problems in society by consensus. Third, the value of being a spiritual person who serves as a spiritual leader who guides people to meet Allah or Woirom. Meanwhile, the value of Demutru as a habitus for building religious life and society includes, first, the field , namely a structured place that forms the strength to unite in society. Second, Habitus contributes to forming a meaningful life of mutual respect and acceptance. Third, the value of capital shown in the social sector is visible through the harmonious life between religious communities in society.